PELATIHAN SANTRIWATI DI LINGKUNGAN PA&PONPES BINA INSANI MELALUI TEKNIK DECOUPAGE PADA DOMPET DAN TAS ANYAMAN - Uju Suji’ah; Sudati Nur Sarfiah; Herdiana Anggrasari; Endang Tri Wahyuni (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
The aim of this PKM activity is to provide training in decoupage technique skills for woven wallets and bags. The target audience for the activity was female students from the Bina Insani Orphanage & Islamic Boarding School, attended by 35 people. The method used in this activity is a lecture and discussion/question and answer, starting with a presentation of the initial material, namely an explanation of entrepreneurship to motivate participants to be interested in entrepreneurship, the next material presentation is an introduction to decoupage by providing an explanation of how to decorate wallets and woven bags using decoupage techniques, and continues with practice. This activity is in collaboration with Rizqun Minallah (RizMina), which is a community empowerment community in the field of skills and crafts as well as providing assistance to participants after the completion of this activity. The results of the skills training presented by many people showed that there were participants other than female students, because the types of activities provided by the service were very directly related to items used daily, namely woven wallets/bags, so they were very enthusiastic about taking part in this activity, and the participants were able to practice the explanations. from the theory given even though it is not perfect. This training inspired participants to become entrepreneurs, and was useful because participants gained additional knowledge regarding how to decorate woven wallets and bags using decoupage techniques